Penentuan Debit Banjir Rancangan Sungai Saluki Kabupaten Sigi dengan Metode HSS SCS - Yosephina Puspa Setyoasri; Dantje Kardana Natakusumah (Journal of Applied Civil Engineering and Infrastructure Technology, 2026)
This study aims to determine the design flood discharge as the basis for planning the construction of a sabo dam on the Saluki River. The sabo dam is intended to protect the existing weir structure and ensure the sustainability of raw water supply in the Pasigala region (Palu, Sigi, Donggala). The 7.4-magnitude earthquake that struck on September 28, 2018, had a severe impact on infrastructure in Central Sulawesi, including water resources facilities along the Saluki River. As part of post-disaster rehabilitation and reconstruction efforts, a weir and intake structure were built to meet raw water needs. However, the Saluki River—classified as a third-order river within the Palu watershed—carries sediment and debris during flood events, posing a threat to infrastructure. Debris flow is a hazardous phenomenon involving a high-speed mixture of water, mud, gravel, and rocks that can damage downstream structures. Therefore, constructing a sabo dam upstream of the weir is essential. This preliminary study employed hydrological analysis using the Synthetic Unit Hydrograph method of the Soil Conservation Service (SCS-UH) to estimate the design flood discharge, considering the limited rainfall data in the area. The analysis resulted in flood discharges for various return periods: Q2 = 116.14 m³/s; Q5 = 158.15 m³/s; Q10 = 185.97 m³/s; Q25 = 221.12 m³/s; Q50 = 247.19 m³/s; and Q100 = 273.08 m³/s. These values serve as a reference for designing the sabo dam, analyzing sediment transport and storage capacity, and developing flood mitigation strategies for the Saluki River sub-watershed.